Assessment of functional impairment after knee anterior cruciate ligament reconstruction using cardiorespiratory parameters: a cross-sectional study - Andrade, Marília Santos (BioMed Central, 2014)
BACKGROUND: A dynamic sub-maximum exercise with the same absolute intensity, performed with different muscle groups, may present exacerbated cardiorespiratory responses. Therefore, cardiorespiratory responses to unilateral exercise may identify bilateral differences. The purpose of this study was to verify whether the cardiorespiratory responses to lower limb exercise display counter-lateral differences, and if they could be used to assist athletes and health professionals involved in rehabilitation. METHODS: Nine individuals participated in this cross-sectional study. They had been treated in a private rehabilitation clinic and submitted to intra-articular reconstruction of the anterior cruciate ligament. The cycling exercise with the same sub-maximal intensity and with one lower limb was used to gather data. Cardiorespiratory responses to exercise were compared between exercises performed with the involved and uninvolved limb after five minutes of exercise. RESULTS: Cardiorespiratory responses to exercise performed with the involved limb presented higher values after five minutes of cycling: oxygen uptake (+7%), carbon dioxide production (+10%)(,) minute ventilation (+20%), breathing frequency (+19%), ventilatory equivalent for oxygen (+14%), end-tidal pressure of O(2) oxygen (+4%), end-tidal pressure of O(2) carbon dioxide (-9%) and heart rate (+9%). CONCLUSIONS: The exacerbated responses, including increase of the ventilatory equivalent and decrease of end-tidal pressure of carbon dioxide(,) indicate that this exercise protocol may be useful in the characterization of the functional deficit of the surgical limb during rehabilitation.